The politics of water supply: the history of Cape Town's water supply 1840-1920 - Grant, Duncan (Department of Historical Studies, 2019)
This dissertation examines the development of Cape Town's water supply between 1840 and 1920. The thesis examines the effect that the augmentation water supply had on municipal politics and the development of the municipality of Cape Town. It is argued that the high cost of water supply, arising out of Cape Town's geographic situation, had a major impact on its municipal government. In the nineteenth century the dominant class was divided between merchants who wanted water and the rentier classes who had to pay for it. In the subsequent political struggle for control of the municipality, the working class, which supported the rentier class were alienated. As a result, they resisted municipal improvement, delaying a solution to the water problem until the twentieth century. Chapter One examines the period from 1840 to 1900 where water supply was related to attempts to bring about municipal and sanitation reform. While this succeeded, by the late 1890's ratepayers reacted against excessive municipal spending, ultimately to the detriment of planned water schemes in the hinterland. Chapter Two argues that in the period between 1900 and 1910 businessmen attempted to link water supply to the unification of the municipalities of the Cape Peninsula. This resulted in a struggle between the city and the suburbs for over the control of the water resources of the hinterland. Chapter Three examines municipal unification in 1913 and the repercussions it had for water supply. The focus falls on a municipal referendum in 1917 in which the class divisions of half a century were a factor in the choice of a hinterland water scheme. The dissertation concludes that water is important for explaining class divisions in municipal politics. It is suggested that the impact of water on municipal history is not unique, but in Cape Town's experience it was prolonged and intense. A further conclusion is that it affected the process of municipal unification between 1902 and 1913, shaping the form of the modern city. A wide range of sources were used including municipal archive material and government reports and commissions. Newspapers and cartoons have been used extensively as they were instruments in the struggle for reform. Comparisons are drawn with the experience of overseas cities in an attempt to provide a coherent model for understanding the place of water supply in urban history. The dissertation represents an attempt to provide a better understanding of Cape Town's history during this period and therefore relates municipal history to wider political, economic and social changes taking place. It also complements recent histories on sanitation, race and municipal politics which fall in this period.